TEACHER’S STRATEGIES IN TEACHING READING AT SMP SWASTA MULIA PRATAMA MEDAN - Yosi D Lumban Gaol; Ribka Debora Greace N; Bellaudry Sri Anzelina (UIN Alauddin Makassar, 2019)
Teacher’s strategies in teaching reading is an attempt to attract students’ attention to learn reading comprehension in the classroom. This research was conducted to find out the strategies of the teacher in teaching reading at SMP Swasta Mulia Pratama Medan and how the teacher applied the strategies in teaching reading, also the reason of the teacher applied the strategies. The researchers used descriptive qualitative method. The subject of this research was English teacher at seven grade of this school. The instruments of this research were classroom observation and interview. The researchers find out the teacher’s strategies in teaching reading, namely Reciprocal Teaching Strategy and QAR strategy. The teacher used these kinds of strategies to make students focus and can easily understand the meaning of the texts, and the teacher also can easily teach reading in the classroom.ABSTRAKStrategi mengajar membaca adalah usaha yang digunakan guru dalam menarik perhatian siswa untuk belajar membaca di kelas. Penelitian ini dilakukan untuk mengetahui strategi guru dalam mengajar membaca di SMP Swasta Mulia Pratama Medan dan bagaimana guru menerapkan strategi dalam mengajar membaca serta alasan guru menerapkan strategi tersebut. Peneliti menggunakan metode deskriptif kualitatif. Subjek penelitian ini adalah guru bahasa Inggris di kelas tujuh di sekolah tersebut. Instrumen penelitian ini adalah observasi kelas dan wawancara. Peneliti menemukan strategi guru dalam mengajar membaca, yaitu Strategi Pengajaran Reciprocal dan strategi QAR. Guru menggunakan kedua strategi ini agar siswa lebih fokus dan dapat dengan mudah memahami makna teks, dan guru lebih mudah untuk mengajar membaca di kelas. Keywords: Strategi, mengajar, membaca